The chemistry in clumpy AGB outflows. Issue Volume 14:Issue S343(2019) (August 2018) - Van de Sande, M.; Sundqvist, J. O.; Millar, T. J.; Keller, D.; Decin, L.
Abstract: The chemistry within the outflow of an AGB star is determined by its elemental C/O abundance ratio. Thanks to the advent of high angular resolution observations, it is clear that most outflows do not have a smooth density distribution, but are inhomogeneous or "clumpy". We have developed a chemical model that takes into account the effect of a clumpy outflow on its gas-phase chemistry by using a theoretical porosity formalism. The clumpiness of the model increases the inner wind abundances of all so-called unexpected species, i.e. species that are not predicted to be present assuming an initial thermodynamic equilibrium chemistry. By applying the model to the distribution of cyanopolyynes and hydrocarbon radicals within the outflow of IRC+10216, we find that the chemistry traces the underlying density distribution.